Global prevalence of platelet-type von Willebrand disease - Omid Seidizadeh; Andrea Cairo; Maha Othman; Flora Peyvandi (Research and Practice in Thrombosis and Haemostasis, 2025)
Background: Platelet-type von Willebrand disease (PT-VWD) is a rare autosomal dominant disorder. It is caused by gain-of-function gene variants in the platelet GP1BA, which results in excessive binding between GPIbα and von Willebrand factor (VWF). The prevalence of PT-VWD is unknown. Objectives: To establish the worldwide and within distinct ethnic groups prevalence of PT-VWD. Methods: We used available exome and genome sequencing data of 807,162 (730,947 exomes and 76,215 genomes) subjects from the Genome Aggregation Database (gnomAD-v4.1). Results: Among the 1,614,324 alleles analyzed in the gnomAD population, there were 1397 distinct GP1BA variants. Of them, 4 variants (p.Arg127Gln, p.Leu194Phe, p.Gly249Val, and p.Met255Ile) have been previously reported to cause PT-VWD. Considering these 4 known pathogenic variants, we estimated a global PT-VWD prevalence of 136 cases/106. The highest estimated prevalence of PT-VWD was found in Africans/African Americans (160/106), Finnish (156/106), Europeans (149/106), and South Asians (110/106), followed by Ashkenazi Jewish (68/106) and East Asian (45/106) ethnicities. In the population with no assigned ethnicity, a prevalence of 126/106 was estimated. Since no pathogenic GP1BA variants that were previously reported to cause PT-VWD were found in Admixed American and Middle Eastern ethnicities, we were unable to estimate the PT-VWD prevalence in these 2 populations. We found a global prevalence of 2.5/106 for severe PT-VWD and 134/106 for the mild form. Conclusion: This population-based genetic epidemiology analysis indicates a substantially higher than expected frequency of PT-VWD. This novel finding suggests that a large number of PT-VWD patients are still under- or misdiagnosed.